1990
DOI: 10.1002/j.1460-2075.1990.tb07512.x
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei: constitutive activity of the VSG and procyclin gene promoters.

Abstract: The variant surface glycoprotein (VSG) and procyclin are the major surface proteins of the bloodstream and procyclic stages, respectively, of Trypanosoma brucei. The promoter regions of the VSG and procyclin gene transcription units could be mapped thanks to the specific enrichment of initial transcripts that occurs following UV irradiation. Whereas the VSG gene is 45 kb distant from its promoter, procyclin genes are located immediately downstream. We show, by run‐on assays on isolated nuclei and by cDNA analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
133
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(151 citation statements)
references
References 38 publications
17
133
0
1
Order By: Relevance
“…The control of VSG gene expression during the parasite life cycle has been more extensively investigated using nuclear run-on assays. Several groups have shown that, although VSG mRNAs are not detected in procyclic forms, transcription initiation does occur at a low level from many, if not all, ES promoters (27)(28)(29). This is consistent with the observation of CAT or luciferase expression under the control of VSG gene promoters cloned in episomal vectors in transiently transfected procyclic parasites (29,30).…”
Section: Smr Teixeirasupporting
confidence: 71%
See 1 more Smart Citation
“…The control of VSG gene expression during the parasite life cycle has been more extensively investigated using nuclear run-on assays. Several groups have shown that, although VSG mRNAs are not detected in procyclic forms, transcription initiation does occur at a low level from many, if not all, ES promoters (27)(28)(29). This is consistent with the observation of CAT or luciferase expression under the control of VSG gene promoters cloned in episomal vectors in transiently transfected procyclic parasites (29,30).…”
Section: Smr Teixeirasupporting
confidence: 71%
“…Several groups have shown that, although VSG mRNAs are not detected in procyclic forms, transcription initiation does occur at a low level from many, if not all, ES promoters (27)(28)(29). This is consistent with the observation of CAT or luciferase expression under the control of VSG gene promoters cloned in episomal vectors in transiently transfected procyclic parasites (29,30). However, when VSG promoters were further analyzed within their chromosomal context, instead of plasmid vectors, it was found that the transcription elongation step is subjected to stage-specific regulation, i.e., the active VSG gene is fully transcribed in bloodstream parasites but most transcriptional activity stops within 1 kb of the VSG promoter in procyclics (27)(28)(29).…”
Section: Smr Teixeiramentioning
confidence: 99%
“…This conclusion is also true in procyclic forms, where the ES promoters are normally not active (38). The very simple structure and ribosomal nature of the ES promoters (39,40) is in keeping with the absence of regulatory sequences. In support of this notion, promoters from active or inactive ESs share the same sensitivity to DNase (24), and antigenic variation still occurs properly if the promoter of the active ES is replaced by the ribosomal promoter (41,42).…”
Section: Discussionmentioning
confidence: 76%
“…Firstly, THT1 and THT2 RNAs (17,32,39,43). Northern blot analysis using THT1-and THT2-specific probes detected a 5-kb mRNA corresponding to a doublet of THT precursor mRNA probably derived from polycistronic transcription (data not shown).…”
Section: Discussionmentioning
confidence: 94%